An Analysis of Early Childhood Education Curriculum Development in Singapore and Finland - Meilasari, Devi; Sukiman, Sukiman; Ukhtiani, Mia Revi; Wati Fajzrina, Lati Nurliana; Febyarum, Lintang; Sari, Diana Martharita; Insiyah, Ma'fiyatun (Universitas Islam Negeri Raden Intan Lampung, 2023)
The curriculum is an important factor in organizing the teaching and learning process to achieve goals. One way to improve educational standards is to implement an effective and innovative curriculum in early childhood education institutions. This research aims to analyze the early childhood education curriculum in Singapore and Finland. The author uses a type of library research. In this research, the author used the data collection instrument by reviewing documents from several books, articles, journals, laws of the Republic of Indonesia, and the Singapore and Finnish curriculum frameworks as literature that supports this research. Data analysis starts with data collection, reduction, presentation, and conclusion. The results of the research show that the education curriculum in Singapore and Finland is included in the category of an advanced education system in terms of the welfare of society or its population (education and economy), the quality of educators or teachers, and the focus on children's future development. The novelty of the analysis results is that in terms of review, it relates to curriculum objectives, content/material, learning media (facilities and infrastructure), learning strategies, and evaluation.